Analisis Alokasi Biaya Bersama Metode Harga Pasar Dalam Menentukan Harga Pokok Produksi Pada UD Rizky - Nurhaflah Soraya; Rubiyani Sitorus (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
This study aims to analyze the allocation of joint costs at UD Rizky, which is a Small and Medium Enterprise producing various types of bread products such as brown bread, sesame brown bread, green bean bread, coconut bread, and also white bread in Air Joman Baru Village, Air Joman District, Asahan Regency. This research is a case study research with data collection techniques through direct observation and interviews. The method used is the market price method where the selling price is unknown at the point of separation. This study found that UD Rizky only estimates the calculation of the cost of goods produced without using any method. So, through the calculation of cost allocation using the market price method, it can be calculated the amount of joint cost allocation of Rp. 20,400,000 which is divided into several types of products proportionally. The market price method is the most effective method  because it has an impact on the cost of production of each product being lower than the selling price set.